Kiat Pemimpin Pendidikan dalam Membangun Komitmen Kerja pada Bawahan - m hurmaini (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Work commitments play an important role to remain upright founding an educational organization. The absence of commitment would be a source of disaster for the continuity of the organization. Therefore, leaders and followers are required to have high work commitment in carrying out the duties and responsibilities of an educational organization to achieve the expected goals. Work Commitment subordinates can be stimulated to be improved, kept or maintained so as not to lose, then educational leaders need to know the various factors that influence/inhibit commitment to the work to subordinates. From the point of psychological aspects, the factors that influence / inhibit commitment to subordinates work include: work motivation, organizational structure, quality management, leadership skills, career development opportunities, compensation, environmental, cultural and organizational values, communication, participation of subordinates in decision-making, appreciation, climate cooperation, the level of wages, job security is good, and praise or awards. Various tips can be a leader in building commitment to work to subordinates, among others: the growing confidence in the leadership and management, able to coordinate their subordinates, and policy leaders are able to give satisfaction to subordinates.